PERAN DINAS PERHUBUNGAN DALAM MENERTIBKAN OKNUM JASA PARKIR LIAR DI KOTA SURABAYA - Dinar Noviantoro; Abraham Ferry Rosando (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
The community benefits greatly from the presence of a parking lot, particularly motor vehicle users who, unsurprisingly, have employed the parking service. So that there are no more disagreements, illegal parking fines must be properly discussed as a criminal. because a lot of individuals are unaware of the regulations governing parking on public highways. The Surabaya City Transportation Service, which is authorized to serve the public by providing guidance and infrastructure facilities in managing traffic on the highway and providing adequate parking for residents of the city of Surabaya, is necessary for the government to play its role in preventing congestion on the road from being used for parking lots